Analisis Masalah Tradisi Dan Budaya Di Era Society 5.0 Dalam Pembelajaran IPS - Sri Mastuti; Suhantoro Suhantoro (FKIP, Universitas Palangka Raya, 2021)
This study aims to determine whether students are aware of various cultural or traditional problems that occur in Madura and are passed down and become knowledge for junior high school students in Sumenep Regency. This research is descriptive, in this case direct observation to four schools in Sumenep Regency and conducting surveys and questionnaires on students' knowledge of Madura's traditions and culture which are still maintained in Era Society 5.0. The contribution of this research is to find out how much knowledge of junior high school students on traditions and culture that is still maintained by junior high school students in four places in Sumenep Regency contained in social studies learning, so that people can understand knowledge about Madura culture and traditions that are still maintained and not eroded by the times. Which continues to develop along with technological advances that make communication between students and the community continues to grow rapidly in the Society 5.0 era. In social studies learning that will be studied also makes surveys in maintaining traditions and culture that have been continuously maintained from generation to generation and continue until now.